Creation of transgenic Brassica napus L. plants expressing human alpha 2b interferon gene - Sakhno, L.O.; Kvasko, O.Y.; Olevinska, Z.M.; Spivak, M.Y.; Kuchuk, M.V. (Цитология и генетика, 2012)
Spring rapeseed transgenic lines expressing human interferon alpha 2b were created by Agrobacteriummediated transformation of aseptic plant leaf explants. The maximum antiviral activity of the leaf extracts reached 4500 IU/g fresh weight. It was determined that the antioxidant activity and the activity of an enzyme of plant antioxidant system – superoxide dismutase (SOD) – in the leaf tissues of transgenic plants increased compared to controls. There were no correlations between the interferon and antioxidant activities, as well as between SOD and interferon activities. Using the obtained transgenic rapeseed plants with high interferon and antioxidant activities as a feed additive for animals might have preventive effect on their body, increasing resistance to infections of various origins.